Risk of meningioma in patients with head injury: A nationwide population-based study - Kuan, A; Chen, Y; Teng, C; Wang, S; Chen, M (Elsevier, 2014)
Background Head injury has been suggested to correlate with meningioma. However, results of studies investigating the relationship between head injury and meningioma were inconsistent. Therefore, we conducted this study to assess the association between head injury and meningioma, and to determine the possible risk factors. Methods Head injury patients aged 18 years and older, without antecedent diagnosis of brain tumor, and who were followed up for more than 30 days between January 1, 2001, and December 31, 2010, were recruited from the Taiwan National Health Insurance Research Database. Hazard ratios (HRs) of meningioma risk for head injury patients compared with an age- and sex-matched cohort were calculated by Cox proportional regression analysis. The difference in cumulative incidence between head injury patients and the matched cohort was analyzed using the Kaplan–Meier method and tested with the log-rank test. Results Each cohort (i.e., the head injury cohort and the matched cohort) consisted of 75,292 individuals with a mean age of 44.7 years, and 52.3% of these patients were male. The incidence rates of meningioma were 3.99/105 person-years and 3.23/105 person-years in the head injury cohort and the comparison cohort, respectively, with a Charlson Comorbidity Index score-adjusted HR of 1.27 (p = 0.514). There were no associations between head injury and risk of meningioma, neither overall nor in stratified analyses according to severity of head injury, age, and sex of patients. Conclusion Head injury, regardless of severity, patient sex, or age, is unlikely to be a cause of meningioma.